Frankenstein - Nobes, Patrick; Shelley, Mary. (Oxford : Oxford University Press, 2007)
A monster assembled by a scientist from parts of dead bodies develops a mind of his own as he learns to loathe himself and hate his creator.
English language and literature.
Keywords: Frankenstein's monster (Fictitious character) -- Juvenile fiction; Monsters -- Juvenile fiction; Monsters -- Fiction; Horror stories; Horror tales